Fishing for Leviathans? Shifting Views on the Liberal State and Development in Peruvian History - Gootenberg, Paul (2013)
This essay examines the shifting conceptions of the state and development through recent waves of Peruvian historiography. The broad structuralist-dependency interpretations of the 1970s and 1980s gave way to a more diffuse and creative ‘political turn’ during and after the 1990s. These changing historical ideas, which still defy synthesis, relate to distinctive global conceptions and phases of economic liberalism, the changing perceived role of states in development, and the integration and social disciplining of a vastly unequal Peruvian nation. Aspects of these Peruvian historical debates may help to shed light on similar controversies through much of the region.